Comparison Between O and OH Intermediates of Cytochrome c Oxidase Studied by FTIR Spectroscopy - Gorbikova, Elena; Kalendar, Ruslan (Frontiers in Chemistry, 2020)
Cytochrome c oxidase is terminal enzyme in the respiratory chain of mitochondria and many aerobic bacteria. It catalyzes reduction of oxygen to water. During its catalysis, CcO proceeds through several quite stable intermediates (R, A, PR/M, O/OH, E/EH). This work is concentrated on the elucidation of the differences between structures of oxidized intermediates O and OH in different CcO variants and at different pH values. Oxidized intermediates of wild type and mutated CcO from Paracoccus denitrificans were studied by means of static and time-resolved Fourier-transform infrared spectroscopy in acidic and alkaline conditions in the infrared region 1800-1000 cm-1. No reasonable differences were found between all variants in these conditions, and in this spectral region. This finding means that the binuclear center of oxygen reduction keeps a very similar structure and holds the same ligands in the studied conditions. The further investigation in search of differences should be performed in the 4000-2000 cm-1 IR region where water ligands absorb.